Problems and Implementation of Internalizing the Panca Jiwa Values of Islamic Boarding Schools in Developing Soft Skills for Student Independence in Islamic Boarding Schools - Amrullah, Fiqih; Supiana, Supiana; Basri, Hasan; Zaqiyah , Qiqi Yuliati (Green Publisher Indonesia, 2025)
Value transformation is a stage that must be carried out by educators to provide information to all students verbally about something good and bad, so that they are able to distinguish between these things and implement these good things in the educational environment. Internalization of values ????integrated with the Pancajiwa of Islamic Boarding Schools is very important to study, because it will obtain an overview of how individuals dialogue with their communities in building morality. The implementation of the Pancajiwa in the lives of students requires a process of strengthening the transformation of the aspects of the educational trilogy, namely Ustad, Kiyai and students so that a mutually reinforcing bond is established and practices the internalization of the Pancajiwa values ????of Islamic Boarding Schools in developing Soft Skills of Student Independence. In this era of globalization, soft skills are becoming increasingly important. Students who have good soft skills will be better prepared to face challenges in the world of work and social life. This study uses a qualitative naturalistic analytical descriptive method, which explains the description or giving meaning systematically, factually and accurately according to reality. The results of the study are the implementation of the Internalization of the Pancajiwa values ????of Islamic Boarding Schools, namely practicing knowledge without having to ask for rewards. The spirit of simplicity practiced in Islamic boarding schools is living simply without excess. The conclusion is that the impact of internalizing the five Islamic values ??of Islamic boarding schools is that all students are able to carry out their studies with sincerity and make the most of their study time. They are able to abandon all their parents' wealth. They can even manage their own study time and get used to doing their own laundry. They also maintain friendships despite being busy with their respective activities. All students even dare to express their opinions, which fosters courage.